Using Innovative Methods in Teaching The Working Mechanism of An Infrared (IR) Spectrometer - Akbar, Abdinazarov; Makhmasaid, Khudayarov; Toshpulatovich, Yuldashev Yusuf (American Journal of Botany and Bioengineering, 2026)
This study examines the working principles of infrared (IR) spectrometers and emphasizes the application of innovative teaching methods in physics education. Fourier transform infrared (FTIR) spectroscopy, which is based on the interference of electromagnetic radiation, is analyzed with particular attention to the operation of the Michelson interferometer. The process of beam splitting, optical path difference formation, interference pattern generation, and Fourier transformation into an absorption spectrum is discussed in detail. In addition, the research highlights the importance of integrating modern pedagogical approaches into the teaching of complex physical concepts such as wave interference and spectroscopic analysis. Innovative methods, including interactive simulations, visual demonstrations, and problem-based learning, are considered as effective tools for improving students’ conceptual understanding and engagement. The results indicate that the use of these methods significantly enhances the quality of education, facilitates deeper comprehension of abstract physical phenomena, and increases students’ interest in the subject. The study concludes that combining theoretical knowledge with innovative teaching strategies is essential for effective physics instruction, particularly in topics related to modern optical and spectroscopic technologies.